Joint video/depth bit allocation for 3D video coding based on distortion of synthesized view - Gaofeng Zhu; Gangyi Jiang; Mei Yu; Fucui Li; Feng Shao; Zongju Peng (IEEE international Symposium on Broadband Multimedia Systems and Broadcasting, 2012)
The joint coding of texture videos and depth maps plays a practical importance in three dimensional (3D) video system. Besides coding efficiency, the strategy of bit allocation between texture videos and depth maps is key issue. The paper firstly analyses the impacts on the quality of virtual views from the joint coding of texture videos and depth maps. Then the paper explores the relationship and establishes a quadratic model between texture video quantization step Q t and depth map quantization step Q d . Consequently, the paper proposes a joint bit allocation scheme based on the model to get the optimal quality of the synthesized views. Experimental results show that the proposed scheme has a better rate-distortion (RD) performance for the synthesized views, compared with fixed bits ratio between texture videos and depth maps, i. e. 5:1.